Analisis Neraca Massa Penyisihan Ion Timbal (Pb²⁺) oleh Bioadsorben Daun Rami pada Sistem Adsorpsi Batch - Rania Nurlita Sari; Raden Kokoh Haryo Putro; Yerry Kahaditu Firmansyah (Fakultas Teknik Universitas Cenderawasih, 2026)
Lead (Pb²⁺) contamination in wastewater is a major environmental concern due to its toxicity, persistence, and ability to accumulate in living organisms. Adsorption using biomass-based materials has been developed as an alternative treatment method because it is efficient, economical, and environmentally friendly. This study aimed to analyze the effect of bioadsorbent dosage and contact time on Pb²⁺ removal efficiency and evaluate Pb²⁺ mass distribution using mass balance analysis in a batch adsorption system. Ramie leaf (Boehmeria nivea) was utilized as a bioadsorbent due to its lignocellulosic content, which provides active sites for metal ion adsorption. The research was conducted experimentally through bioadsorbent preparation, chemical activation, and batch adsorption using artificial Pb²⁺ solutions with variations in bioadsorbent dosage and contact time. Pb²⁺ concentrations before and after adsorption were analyzed using Atomic Absorption Spectroscopy (AAS). The obtained data were used to determine removal efficiency and Pb²⁺ distribution between the liquid phase and bioadsorbent. The results showed that ramie leaf bioadsorbent effectively reduced Pb²⁺ concentration, with the optimum condition obtained at 4 g/L bioadsorbent dosage and 90 minutes contact time, achieving 98.46% removal efficiency. Mass balance analysis indicated that Pb²⁺ ions were successfully transferred from the solution phase onto the bioadsorbent surface. These findings demonstrate that ramie leaf bioadsorbent has potential as a sustainable alternative material for heavy metal removal in wastewater treatment.